2019
DOI: 10.1371/journal.pone.0214962
|View full text |Cite|
|
Sign up to set email alerts
|

Intimate partner violence and its associated factors among pregnant women in Bale Zone, Southeast Ethiopia: A cross-sectional study

Abstract: Background Intimate partner violence (IPV) against women is a major public health concern in low income countries. Violence against pregnant women has adverse effects on maternal and newborn outcomes. This study aimed to assess the prevalence and associated factors of intimate partner violence in Southeast Ethiopia pregnant women. Methods Institutional based cross-sectional study was conducted on pregnant women who were attending antenatal care (ANC) in Bale Zone health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
59
3
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(92 citation statements)
references
References 23 publications
17
59
3
5
Order By: Relevance
“…This finding is similar to the previous study conducted in Gondar Hospital, which reported a prevalence of sexual IPV of 2.4% [42]. However, a higher prevalence of sexual IPV among pregnant women was reported by other studies from Ethiopia that were conducted in Jimma (30%) [16], Debre-Berhan (19.8%) [17], Hulet Ejju Enessie district (14.8%) [43], and Bale Zone (36.3%) [18]. The low prevalence of sexual IPV in the current study might be attributed to women's strong disapproval of sexual violence as more than 99% of women in this study believed that women had the right to refuse sex.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is similar to the previous study conducted in Gondar Hospital, which reported a prevalence of sexual IPV of 2.4% [42]. However, a higher prevalence of sexual IPV among pregnant women was reported by other studies from Ethiopia that were conducted in Jimma (30%) [16], Debre-Berhan (19.8%) [17], Hulet Ejju Enessie district (14.8%) [43], and Bale Zone (36.3%) [18]. The low prevalence of sexual IPV in the current study might be attributed to women's strong disapproval of sexual violence as more than 99% of women in this study believed that women had the right to refuse sex.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of IPV in this study was similar to that of previous Ethiopian studies that were conducted in Jimma (45%) [16] and Tigray (41%) [35] and findings from other countries that were conducted in Jordan (40.9%) [36], Kenya (37%) [30], Egypt (44.1%) [37] and Portugal (43.4%) [38]. However, it was lower than that of previous studies from Ethiopia that were conducted in Addis Ababa (75.2%) [5] and Bale Zone (59%) [18], but higher than that of previously conducted research in southern Ethiopia (21%) [39]. The lower prevalence of IPV in the current study compared to the previous study from Bale Zone might be due to the difference in measurement of IPV as the study from Bale Zone used a wider definition of IPV that included economic violence, whereas in our study the definition of IPV was limited to physical, sexual, and emotional violence.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Importantly, our findings highlight the association between khat use and IPV and shed light on the mechanisms through which khat use may be a risk factor for IPV. Our findings are consistent with several other studies that report a significant association between male perpetration of IPV and substance use (including khat) [29][30][31]39]. For example, one study among Somali refugee community workers in Dadaab refugee camp in Kenya reported khat use as a driver of GBV [39].…”
Section: Discussionsupporting
confidence: 92%
“…While research on khat use is limited, some evidence suggests adverse health impacts including behavioral and mental health problems [26][27][28]. Several studies have also demonstrated associations between khat use and IPV perpetration [29,30], including among Somali populations [31]. However, there are limited data on mechanisms through which khat use may lead to IPV, and how this relationship may be influenced by displacement.…”
Section: Introductionmentioning
confidence: 99%